A new supramolecular heterosynthon [C-I O&z.dbd;C(carboxylate)] at work: engineering copper acetate cocrystals - Torubaev, Yury V; Skabitsky, Ivan V (CrystEngComm, 2020)
A carboxylate iodine supramolecular heterosynthon can be reliably applied in cocrystal engineering, using metal carboxylates as building blocks. Analysis of the energy framework of the exemplary paddlewheel crystal [Cu(OAc) 2 MeOH] 2 indicates a robust 1D chain and even 2D layer long-range synthon modules, which can be intactly transferred into cocrystals. However, this approach allows the identification of a "weak link" - i.e. layers where the C-H O&z.dbd;C hydrogen bonds between ([Cu(OAc) 2 (MeOH)] 2 ) n polymeric chains will be subject to substitution by I O&z.dbd;C halogen bonds during interaction with halogen bond donor co-formers. In contrast to the O-H O&z.dbd;C/C-H O&z.dbd;C catemeric crystals of pure acetic acid, the crystal design exercise based on the I O&z.dbd;C(carboxyl) supramolecular synthon afforded a 1 : 1 cocrystal of 1,4-C 6 F 4 I 2 and CH 3 COOH, where the discrete centrosymmetric dimers of acetic acid are stabilized by I O&z.dbd;C(carboxyl) halogen bonds. Carboxylate-iodine supramolecular heterosynthons in combination with energy frameworks can be reliably applied in engineering hybrid metal-carboxylate cocrystals.